รูปแบบการดูแลผู้สูงอายุโดยชุมชนท้องถิ่นจัดการตนเอง กรณีศึกษา : องค์การบริหารส่วนตำบลท่างาม อำเภออินทร์บุรี จังหวัดสิงห์บุรี - จันทร์ขำ วริยา; บัวเจริญ หทัยชนก; อาสน์วิเชียร ชินวุฒิ (Area Based Development Research Journal, 2015)
บทคัดย่อไม่สมบูรณ์ Elderly Care System Model by community and local government with self-management Case study : Targnam Sub-district local government, Inburee District, Singburee Province The objectives: This study was qualitative research by Rapid Ethnography Community Assessment Program: RECAP. The objectives were to address social capital and capacity building for developing, organizing and identifying healthy management concepts in elderly care system at Targnam sub-district, Singburi Province. Material and method: Data collection included 1) Document analysis such as basic sub-district data, individual data, community data and Annual report. 2) In-depth interview, focus group, participation and non-participation observation. Purposive selection 105 key informants were local administers, community leader, village leader, head of the group’s volunteers, elderly families, local organization, people in community government officer and stakeholders who involved in transforming healthy Sub-district. Content analysis and matrix method were used for data analysis. Results: 1) Concepts, principle, management and development comprises community participation, sharing vision, solving problems with multi networking, building volunteer. They were management for establishing self-care system, environment development for community health, health care service system and social fund and social welfare with the use of data base. 2)The elderly community care system based-on of local self-management focuses on the use of database, the integration of social capital and potential, both internal and external, the emphasis on quality of life, equality and self-reliance. The system composed of 4 dimensions 1) Long-term care, 2) the development of potential, learning, job and an income of the elderly, 3) the preparation for elderly and 4) the alignment of building and safety environment for elderly and pre-elderly.